Evaluación de la gestión administrativa de los procesos licitatorios y operativos en la empresa Construrbanos S.A.S. (2017)
In this monograph reference is made to the description of the bidding and operating processes of the company Construbanos S.A.S, based on interviews and observation of the processes directly in the company and in the civil works that it currently has; taking into account the detailed analysis of the bidding and operational processes of the company, followed by a table that synthesizes all the analysis carried out to highlight the positive and negative aspects in the processes and to finalize the proposals for improvement for the bidding processes and operatives of Construrbanos SAS, which were made from the analysis, in order to optimize the processes so that the company is more competitive.